Diagnostic Accuracy of Ultrasonography Versus Magnetic Resonance Imaging in the Detection of Endometrial Carcinoma Keeping Histopathology as Gold Standard - Jovaria Ehsan; Ayesha Isani Majeed; M Ehsan ul Haq; Ramish Riaz; Asma Ehsan; Momna Ehsan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To calculate the diagnostic accuracy of Ultrasonography versus Magnetic Resonance Imaging in detecting endometrial carcinoma with histopathology kept as a gold standard.